Avaliação da cinética de liberação de nitrogênio a partir de ureia revestida com poliuretano em diferentes espessuras - Araújo, Michele Morais (2022)
Among the nitrogen fertilizers, the most used worldwide is urea, with 46% of nitrogen, but losses by volatilization and leaching can reach up to 60%. Controlled-released fertilizers have semi-permeable layers on their surface that control the nutrients release, minimizing losses. The present study carried out coatings with polyurethane and calcium sulfate in mass percentages of 4, 6, 8, 10 and 12% and solubilization in water. The MEV images showed coverings without structural damage, but rough due to the presence of calcium sulfate. The coatings had thicknesses of 20,63 ± 7,34, 36,01 ± 9,74, 41,90 ± 7,92, 52,56 ± 7,67 and 65,05 ± 7,08 μm. The thickness increment increased the release delay reaching 90% at 6 h for 4% coating and 291 h to 12%. Uncoated urea achieved complete release in approximately 4 min. The release process presented diffusivity as the main mechanism and the kinetic adjustments that best described the release process were the Modified Hyperbole models, Peppas and Sahlin and Korsmeyer-Peppas. The empirical model with thickness dependence from the Modified Hyperbola model best described the release process for polyurethane-covered urea. For uncoated urea, the peppas and sahlin model dependent on thickness showed better results. The neural model significantly represented the experimental results for coated urea, but not for uncoated urea due to rapid release for this condition.